2016
DOI: 10.18544/pedm-22.01.0045
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of diabetes type 1 in children aged 0-14 in Podlasie Province in years 2005-2012

Abstract: 1. The DMT1 incidence rate among children aged 0-14 years, in Podlasie Province, during 2005-2012 years was 20,84/100 000. 2. Increase in incidence rate was observed in the studied period from 15,23/100 000 in 2005 to 26,71/100 000 in 2012. The highest increase in incidence rate, 2,5 times, was fund in the youngest group, aged 0-4 years. 3. The seasonal incidence of New onset was observed with the greater number in autumn-winter months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Our study showed a sinusoidal seasonal pattern in the incidence of T1D with a lower number of children diagnosed in spring-summer and a higher frequency in autumn-winter. Similar to our results other authors confirmed the seasonality in the incidence of T1D [7,[11][12][13][14][15][16][17]. However, no significant seasonality was observed in some studies [7,18,19].…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed a sinusoidal seasonal pattern in the incidence of T1D with a lower number of children diagnosed in spring-summer and a higher frequency in autumn-winter. Similar to our results other authors confirmed the seasonality in the incidence of T1D [7,[11][12][13][14][15][16][17]. However, no significant seasonality was observed in some studies [7,18,19].…”
Section: Discussionsupporting
confidence: 91%
“…According to the large nationwide studies, in Poland, incidence of T1D is also increasing year after year ( 6 ). In the previous study considering our region, the lowest IR was observed in the youngest group of children aged (0–4 years), whereas the highest IR was identified in older children (10–14 years) ( 21 ). American SEARCH for Diabetes in Youth, a multicenter study of American population, also confirmed this phenomenon (an incidence of 33.9/100,000 between 10 and 14 years old, regardless of ethnic group and region of residence).…”
Section: Discussionmentioning
confidence: 54%
“…In this case, small intestine-associated autoimmunity was recognized. The CD was diagnosed on the basis of the revised criteria of CD diagnosis according to the European Society Pediatric Gastroenterology, Hepatology, and Nutrition criteria (21,23) and always consulted with experienced gastroenterologist. Patients positively serologically tested for tTGA, EMA, and ARA had a gastroscopy performed if needed for diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of type 1 diabetes is associated with the destruction of pancreatic B cells by the immune system of the owner. The result is a lack of insulin in the patient's body, which leads to hyperglycemia [5,6,7]. As indicated by the Polish Diabetes Association of 2018, chronic hyperglycemia may lead to damage, insufficiency and impairment of many different organs, in particular: eyes, kidneys, heart, blood vessels and nervous system [5].…”
Section: Introductionmentioning
confidence: 99%